Integrating GEO Database, Mendelian Randomization, and Molecular Docking to Identify HLA-C as a Potential Therapeutic Target for Periodontitis - ChengJi Shi; Xinyi Ou; LiJuan Huang; XiaoXu Lei; ShuHao Xu; Menglu Ou; Wei Li; Xi Zhao (Mediators of Inflammation, 2025)
Conclusion: This study identifies HLA-C as a potential therapeutic target for periodontitis, with MD studies and molecular dynamic simulations highlighting metronidazole as a potential treatment. These findings provide new insights into periodontitis pathogenesis and potential therapeutic strategies.